Side-Stream Based Marine Solubles From Atlantic Cod (Gadus morhua) Modulate Appetite and Dietary Nutrient Utilization in Atlantic Salmon (Salmo salar L.) and can Replace Fish Meal - Hanne Jorun Sixten; Ivar Rønnestad; André S. Bogevik; Tone Aspevik; Åge Oterhals; Ana S. Gomes; Floriana Lai; Ingvill Tolås; Virginie Gelebard; Marie Hillestad; Katerina Kousoulaki (Aquaculture Nutrition)
Whitefish fisheries’ side-stream biomass is an abundant underutilized resource that can be valorized to benefit future aquaculture sustainability. Four novel ingredients based on side-streams from Atlantic cod (Gadus morhua) fileting were produced. FM-hb, a fish meal (FM), and FPH-hb, a fish protein hydrolysate based on heads (h) and backbones (b); FM-hbg, a FM based on heads, backbones, and viscera/guts (g); and FPC-g, a fish protein concentrate based on viscera preserved in formic acid. Four diets were prepared containing one of the ingredients replacing 50% of the dietary FM protein, in addition to a positive (FM10) and a negative (FM5) control. The six diets were fed to triplicate tanks with Atlantic salmon (Salmo salar L.; 113 ± 1 g) over 8 weeks. Besides general performance, gut and brain gene expression for selected hormones and key neuropeptides involved in the control of appetite and digestive processes were studied during feeding and postprandial, and possible reference levels for Atlantic salmon were established. All side-stream-added diets performed well, with no significant differences in performance and biometrics between the treatments. Some gene expression differences were observed, but no well-defined patterns emerged supporting clear dietary effects related to digestive performance or appetite. However, in the brain, a short-time upregulation of agouti-related protein-1 (agrp1), corresponded to higher cumulative feed intake (FI) for the FM10 diet supporting notions that this may be a candidate biomarker for appetite in salmon. Expression of stomach ghrelin-1 (ghrl1) was higher than ghrelin-2 (ghrl2) and membrane-bound O-acyltransferase domain-containing 4 (mboat4), and midgut peptide YYa-2 (pyya2) and glucagon-a (gcga) were higher than peptide YYb-1 (pyyb1). A comparison showed that midgut peptide YYa-1 (pyya1), pyya2, and gcga expressions were higher than in the hindgut, which is opposite of what is found in mammals. In conclusion, this study shows that sustainable side-stream raw materials with different characteristics can partly replace high-quality commercial FMs giving similar performance.